Brownies a base de chocolate sustituyendo de forma parcial la harina de trigo (Triticum sativum) por harina de quinua (Chenopodium quinoa)” - Zambrano Zambrano , Fernanda Aly (2023)
In pastry, the Brownie can be defined as a type of sponge cake or a small chocolate cake which has among its main ingredients; Wheat flour, chocolate, eggs, sugar and butter, however it is increasingly necessary to improve the nutritional profile of bakery products, for this reason the inclusion of quinoa flour is proposed as a constituent that replaces wheat flour in a percentage , with which we estimate that we can obtain a good quality product with a higher nutritional value. Due to the aforementioned, this research work aims to examine the effect of the partial substitution of wheat flour (Triticum sativum) by quinoa flour (Chenopodium quinoa) on the pHysicochemical, microbiological, sensory characteristics and production cost of brownies. chocolate based.